2002
DOI: 10.1590/s1516-35982002000400022
|View full text |Cite
|
Sign up to set email alerts
|

Farelo de girassol na alimentação de suínos em crescimento e terminação: digestibilidade, desempenho e efeitos na qualidade de carcaça

Abstract: RESUMO -Foram realizados dois experimentos, objetivando avaliar o farelo de girassol (FG) na alimentação de suínos em crescimento e terminação. Inicialmente, foi avaliada a digestibilidade do FG, utilizando-se oito suínos machos castrados, com peso médio inicial de 30,41 kg, alojados individualmente em gaiolas metabólicas. Posteriormente, 48 suínos (Large White x Landrace), sendo 24 machos castrados e 24 fêmeas, foram submetidos, dos 25,82 aos 92,33 kg, a quatro tratamentos: dieta com 0% de FG, dieta com 7% de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
2
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 3 publications
3
10
2
8
Order By: Relevance
“…This is a hormone that decreases intestinal transit (NRC, 1998), thereby increasing the digestibility of nutrients in general and explaining the bettered production performance under high inclusion of this product. Silva et al (2002b) evaluated the inclusion of up to 21.0% sunflower meal in the diets and evidenced no difference during the growing phase. Colina et al (2010) used 17.5% inclusion of sunflower meal in diets for piglets of 15 days of age in their experiment, which suggested that the inclusion of this ingredient can also be used in the starter phase, in spite of its high fiber content.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is a hormone that decreases intestinal transit (NRC, 1998), thereby increasing the digestibility of nutrients in general and explaining the bettered production performance under high inclusion of this product. Silva et al (2002b) evaluated the inclusion of up to 21.0% sunflower meal in the diets and evidenced no difference during the growing phase. Colina et al (2010) used 17.5% inclusion of sunflower meal in diets for piglets of 15 days of age in their experiment, which suggested that the inclusion of this ingredient can also be used in the starter phase, in spite of its high fiber content.…”
Section: Resultsmentioning
confidence: 99%
“…Carellos et al (2005) stated that inclusion of up to 16.0% sunflower meal in fodder diets for finishing pigs would be technically viable, without compromising performance values or carcass characteristics. Silva et al (2002b) evaluated the inclusion of higher levels of SM (21%) in growing and finishing pig fodder and reported no difference in carcass characteristics when using this feed. Additionally, Silva et al (2002b) determined a digestibility value of 73.2% in sunflower meal crude protein.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assim, Silva et al (2002) não verificaram efeito da substituição parcial do milho e farelo de soja pelo farelo de girassol na dieta de suínos nas fases de crescimento I (20 a 50 kg de peso vivo), crescimento II ( entre 50 a 80 kg de peso vivo) e terminação (80 a 120 kg de peso vivo). Os autores concluem que a inclusão de até 21% de farelo de girassol nas dietas de leitões em crescimento e terminação, não influenciou as características de desempenho e de carcaça.…”
Section: Farelo De Girassolunclassified